Sperm epigenomics: challenges and opportunities - Casas, Eduard; Vavouri, Tanya (Frontiers in Genetics, 2014)
Sperm is a highly differentiated cell type whose function is to deliver a haploid genome to the oocyte. The sperm ‘epigenomes’ were traditionally considered to be insignificant - the sperm is transcriptionally inactive, its genome is packaged in sperm-specific protamine toroids instead of nucleosomes, and its DNA methylation profile is erased immediately post-fertilization. Yet, in recent years that has been an increase in the number of reported cases of apparent epigenetic inheritance through the male germline, suggesting that the sperm epigenome may transmit information between generations. At the same time, technical advances have the genomewide profiling of different layers of the sperm epigenome feasible. As a result, a large number of datasets have been recently generated and analysed with the aim to better understand what non-genetic material is contained within the sperm and whether it has any function post-fertilization. Here, we provide an overview of the current knowledge of the sperm epigenomes as well as the challenges in analysing them and the opportunities in understanding the potential non-genetic carriers of information in sperm.